Improvement of Pulmonary Function Measured by Patient-reported Outcomes in Patients With Spinal Muscular Atrophy After Growth-friendly Instrumentation. Issue 1 (January 2021) - Matsumoto, Hiroko; Mueller, John; Konigsberg, Matthew; Ball, Jacob; St. Hilaire, Tricia; Pawelek, Jeff; Roye, David P.; Cahill, Patrick; Sturm, Peter; Smith, John; Thompson, George; Sponseller, Paul; et al.
Abstract : Background: Children with spinal muscular atrophy (SMA) sustain a progressive reduction in pulmonary function (PF) related to both muscular weakness and the concomitant effects of spinal deformity on the thorax. Growth-friendly instrumentation is commonly utilized for younger patients with scoliosis and SMA to halt the progression of spinal curvature, but its effect on PF in these patients has not previously been investigated. Using the change in Early Onset Scoliosis 24-Item Questionnaire (EOSQ-24) PF subdomain scores, the authors will investigate whether PF improves in patients with SMA after a growth-friendly intervention. Methods: This was a multicenter retrospective cohort study from 2 international registries of patients with SMA undergoing spinal deformity surgery from 2005 to 2015. Data collected were age, sex, degree of major coronal curve, type of growth-friendly construct, forced vital capacity (FVC), and EOSQ-24 scores at the patient's preoperative, 1-year postoperative, and 2-year postoperative visits. Differences in EOSQ-24 PF scores and FVC between baseline and postoperative assessment were examined by paired tests. Results: A total of 74 patients were identified (mean age, 7.6±2.3 y, major curve 68.1±22.4 degrees, 51.4% female individuals). The mean EOSQ-24 PF scores improved significantly from 70.6 preoperatively to 83.6 at 1 year ( P =0.092) and 86.5 at 2 years postoperatively ( P =0.020). The scores in patients with rib-based constructs showed steeper increases at 1-year assessments than those in patients with spine-based constructs. The mean paired FVC value decreased from 63.9% predicted preoperatively, to 57.6% predicted at 1 year postoperatively ( P =0.035), and 61.9% predicted preoperatively, to 56.3% predicted at 2 years postoperatively ( P =0.178). Conclusions: Patients with SMA who received growth-friendly instrumentation did experience improvements in PF as measured by EOSQ-24 assessing the caregivers' perception. Given the uncertain reliability of PFTs in this young population, EOSQ-24 is an important tool for measuring improvements in health-related quality of life. Level of Evidence: Level III—retrospective study.